2015
DOI: 10.5543/tkda.2015.11354
|View full text |Cite
|
Sign up to set email alerts
|

Predictive role of left atrial and ventricular mechanical function in postoperative atrial fibrillation: a two-dimensional speckle-tracking echocardiography study

Abstract: The combination of 2D STE, clinical, and biochemical parameters may help predict POAF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 0 publications
1
18
1
7
Order By: Relevance
“…However, β-blockers usage was associated with less incidence of AF. These findings are in agreement with Başaran et al, 16 who reported POAF group weren’t on beta–blockers ( P value <0.001)…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, β-blockers usage was associated with less incidence of AF. These findings are in agreement with Başaran et al, 16 who reported POAF group weren’t on beta–blockers ( P value <0.001)…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, speckle tracking echocardiography revealed that the left ventricular global longitudinal strain (LV GLS %) was significantly reduced in POAF group ( P value <0.001). This is in contrast to Başaran et al, 16 who studied the predictive role of left atrial and ventricular mechanical function in postoperative atrial fibrillation. They reported that the left ventricular global longitudinal strain value was not different between the 2 groups ( P value >0.005).…”
Section: Discussionmentioning
confidence: 71%
“…Advanced age is considered an independent predictor for POAF after cardiac surgery as well as AF incidence outside of the cardiac surgery population. 42 Patients with advanced age experience remodeling in the atrial tissue including changes in ion channel function and distribution, 43 systemic inflammation, 3,6,9,21 impulse propagation, 7,8,10,13 fibrosis distribution, 15,16 and structural substrate, 4,17,19,24 which lead to increased POAF inducibility and burden with increased age. Since age-related remodeling is chronic and slow, older patients undergoing cardiac surgery likely have developed the substrate for increased POAF inducibility and burden.…”
Section: Discussionmentioning
confidence: 99%
“…ПОФП имеет два основных патофизиологических механизма, которые могут быть связаны с размерами ЛП: дегенеративные изменения миокарда предсердий и предоперационные электрофизиологические изменения. Следует учитывать, что предоперационная механическая дисфункция предсердий может сопровождаться развитием ФП в ходе операции, что продемонстрировано в работе Başaran Ö, et al (2016) [11].…”
Section: Discussionunclassified